Interactive Virtual Campus Tour using Panoramic Video: A Heuristic Evaluation - Aznoora Osman; Nur Izlin Iskak; Nadia Abdul Wahab; Norfiza Ibrahim (Journal of Computing Research and Innovation, 2020)
Difficulty in finding the destination around a campus is a common problem faced by students, staffs and visitors of a university. Outdated signboards, confusing building architecture and layout, and bad weathers are just some of the hindrance to find location for people who are unfamiliar with the campus area. To solve the probl em, virtual campus tour is chosen because it can also be embedded into a university website, or use as a stand - alone app. The virtual campus tour app can help users in visualizing their journey around campus because it was developed using collections of pa noramic video footage, which allows user to watch in 360 - degree view of selected campus area. Administrative building, academic blocks and residential college are some of the destinations included in the tour. A heuristic evaluation of system usability was conducted with five university lecturers who have vast experience in the computer science field . The purpose is to identify usability problems in the user interface of the app, by judging its compliance with standard usability principles. Comments from ex perts were used to make refinement before it could be further tested with potential users.